Evaluation of fermented african yam bean (Sphenostylis stenocarpa) and pigeon pea (Cajanus cajan) seed meals in diets of broiler chickens - Abioye, A. A; Ojediran, T. K.; Emiola, I. A. (Nigerian Journal of Animal Science, 2023)
African Yam Bean (AYB) and Pigeon Pea (PP) seeds are rich in crude protein, nitrogen free extract and mineral components, which were marginally enhanced post-fermentation with reduced anti-nutrients. These substrates were fed to a total of 120 1-d old broiler chicks at 50 and 100% replacement for soybean. Five experimental diets were formulated with maize-soybean based diet as the control in a Completely Randomized Design in a 42-day feeding trial. Each treatment consisted of 3 replicates, with 8 birds per replicate. The results showed that there were significant (p<0.05) differences among treatments in average daily feed intake (ADFI), average daily gain (ADG) and feed conversion ratio (FCR). The ADFI and ADG were depressed in birds fed 100% FAYB compared with those fed 50% of either of the two legumes while the FCR of those fed 50% of the substrates compared favourably with the control. Birds fed diets containing 100% FPP had higher digestibilities of Ether Extract and ash compared with those fed 50% FPP but similar to those obtained for birds in the control and FAYB. This study revealed that broiler chicks could tolerate 50% FAYB and FPP without detrimental effect on growth performance.